SISTEM PENDUKUNG KEPUTUSAN PENENTUAN PENERIMA BEASISWA DENGAN METODE SIMPLE ADDITIVE WEIGHTING DI SMPN 19 TANGERANG - Kartiko, Bayu Aji (University of Muhammadiyah Tangerang, 2021)
In determining scholarship recipients in schools manually, errors often occur causing inefficient management of scholarship data in terms of time and the absence of clear criteria for how students can obtain scholarships. To anticipate that mistakes do not occur, a Decision Support System is needed. One method that can be used is the Simple Additive Weighting (SAW) method. The data collection method used was the observation method to the school and the interview method with the related teachers regarding the scholarship acceptance. In this research, system development is carried out using the Waterfall method. And for system testing used Black-box Testing. The system design uses the Unified Model Language (UML), which includes usecase diagrams, activity diagrams, sequence diagrams and class diagrams. Then the program implementation uses the PHP programming language and MySQL database. This application will also display the value, criteria, alternatives and then a ranking of the scholarship recipient determination process. With this decision support system, the school will get the results of who is entitled to receive the scholarship.Â Keywords: Decision Support System, Scholarship, Simple Additive Weighting (SAW) Method, Unified Model Language (UML).